Essence and Elements of the Participant Composition in Administrative Legal Proceedings - Asliddin Azimovich Boltayev (Scientific Trends, 2024)
This article addresses issues related to administrative legal proceedings, focusing on the legal status of parties - the applicant and the respondent. Special attention is given to the procedural capacity and legal capacity of parties in the context of administrative processes. The article also examines existing problems in administrative legal proceedings, emphasizing the significance of the pro bono concept in ensuring access to justice. It highlights the experience of legal decisions in the field of administrative legal proceedings and their impact on the further development of this area. Another important aspect of the article is the analysis of proposals for improving legislation aimed at enhancing the efficiency of the administrative legal process and ensuring broader citizen access to justice.
Keywords: Administrative legal proceedings, legal status of parties - applicant and respondent, procedural capacity and legal capacity of parties, problems, pro bono, legal decisions, legislation improvement.